Utilization of Eucalyptus Oil Refineries Waste for Cement Particle Board - Setiadji, Rudi; Husin, Andriati Amir (International Journal of Sustainable Construction Engineering and Technology, 2012)
Utilization of eucalyptus oil refinery waste in the manufacture of building material component of cement particle board is expected to reduce the price of housing units. This research used laboratory experimental methods, eucalyptus oil waste in the form of branches an twigs from eucalyptus tree. The variation of the testing were mixtures composition of the particle : cement, additives as accelerators, cold press load during manufacture of cement particle board. Cold press duration of cement board was 24 hours. The size of particle boards were (40 x 40) cm2 and 13 mm thick. The samples were tested for its density, water content, water absorption, flexural strength, thickness swelling, adhesion strength, and the nails pull out strength.